Modelling and in vivo evaluation of tendon forces and strain in dynamic rehabilitation exercises: a scoping review - Antonio I Cuesta-Vargas; Adrian Escriche-Escuder; Jose Casaña (BMJ Open)
Objectives Although exercise is considered the preferred approach for tendinopathies, the actual load that acts on the tendon in loading programmes is usually unknown. The objective of this study was to review the techniques that have been applied in vivo to estimate the forces and strain that act on the human tendon in dynamic exercises used during rehabilitation.Design Scoping review.Data sources Embase, PubMed, Web of Science and Google Scholar were searched from database inception to February 2021.Eligibility criteria Cross-sectional studies available in English or Spanish language were included if they focused on evaluating the forces or strain of human tendons in vivo during dynamic exercises. Studies were excluded if they did not evaluate tendon forces or strain; if they evaluated running, walking, jumping, landing or no dynamic exercise at all; and if they were conference proceedings or book chapters.Data extraction and synthesis Data extracted included year of publication, study setting, study population characteristics, technique used and exercises evaluated. The studies were grouped by the types of techniques and the tendon location.Results Twenty-one studies were included. Fourteen studies used an indirect methodology based on inverse dynamics, nine of them in the Achilles and five in the patellar tendon. Six studies implemented force transducers for measuring tendon forces in open carpal tunnel release surgery patients. One study applied an optic fibre technique to detect forces in the patellar tendon. Four studies measured strain using ultrasound-based techniques.Conclusions There is a predominant use of inverse dynamics, but force transducers, optic fibre and estimations from strain data are also used. Although these tools may be used to make general estimates of tendon forces and strains, the invasiveness of some methods and the loss of immediacy of others make it difficult to provide immediate feedback to the individuals.